2018
DOI: 10.3389/fendo.2018.00460
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1, Metabolism, and Diabetes in the Embryonic and Adult Heart

Abstract: The heart is able to metabolize any substrate, depending on its availability, to satisfy its energy requirements. Under normal physiological conditions, about 95% of ATP is produced by oxidative phosphorylation and the rest by glycolysis. Cardiac metabolism undergoes reprograming in response to a variety of physiological and pathophysiological conditions. Hypoxia-inducible factor 1 (HIF-1) mediates the metabolic adaptation to hypoxia and ischemia, including the transition from oxidative to glycolytic metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 145 publications
(163 reference statements)
2
73
0
Order By: Relevance
“…Some studies showed that cells cultured in high glucose concentration medium present with decreased levels of HIF-1α. This led to a consensus that hyperglycemia was responsible for decreased HIF-1α protein levels (Xiao et al, 2013;Cerychova and Pavlinkova, 2018). Investigation of the effect of certain glucose concentrations on HIF-1α expression in human dermal fibroblasts (HDF) at normoxia and hypoxia showed that HIF-1α expression depends on glucose concentration only in hypoxia.…”
Section: Gapdhmentioning
confidence: 99%
“…Some studies showed that cells cultured in high glucose concentration medium present with decreased levels of HIF-1α. This led to a consensus that hyperglycemia was responsible for decreased HIF-1α protein levels (Xiao et al, 2013;Cerychova and Pavlinkova, 2018). Investigation of the effect of certain glucose concentrations on HIF-1α expression in human dermal fibroblasts (HDF) at normoxia and hypoxia showed that HIF-1α expression depends on glucose concentration only in hypoxia.…”
Section: Gapdhmentioning
confidence: 99%
“…HIF-2α and HIF-3α are found in vertebrates and are expressed in a cell-type specific manner (Semenza, 2020). HIF-1α has been shown to be essential to embryonic development (Cerychova and Pavlinkova, 2018), and HIF-2α is noted for regulation of EPO transcription, to produce erythropoietin (EPO) protein postnatally in the kidney (Gruber et al, 2007;Haase, 2013). While these transcription factors regulate thousands of genes, the roles of HIF-3α remain to be extensively characterized (Yang S. L. et al, 2015;Duan, 2016).…”
Section: Hypoxia Signaling and The Hif Pathwaymentioning
confidence: 99%
“…Growing interconversion of lactate and pyruvate is greatly increased and upregulates CNDP1 which is necessary for carnosine uptake [55,56]. The inhibited fatty acid oxidation concatenated by the hypoxia condition inducing hypoxia-inducible factor-1 (HIF-1) which triggers glycolysis in T2DM and GDM patients [57]. In turn, oxidative damage caused by lactate interconversion evokes the rising up-regulation of CRP as a protective response to defense against oxidative stress and subsequent chronic inflammation condition.…”
Section: Discussionmentioning
confidence: 99%